Integration Questions

Question Number 122748 by bemath last updated on 19/Nov/20

$$\:\:\underset{\mathrm{0}} {\overset{\mathrm{3}} {\int}}\:\frac{{dx}}{\left(\mathrm{3}−{x}\right)\sqrt{{x}^{\mathrm{2}} +\mathrm{1}}}\:? \\$$

Answered by MJS_new last updated on 19/Nov/20

$$\int\frac{{dx}}{\left(\mathrm{3}−{x}\right)\sqrt{{x}^{\mathrm{2}} +\mathrm{1}}}= \\$$$$\:\:\:\:\:\left[{t}={x}+\sqrt{{x}^{\mathrm{2}} +\mathrm{1}}\:\rightarrow\:{dx}=\frac{\sqrt{{x}^{\mathrm{2}} +\mathrm{1}}}{{x}+\sqrt{{x}^{\mathrm{2}} +\mathrm{1}}}\right] \\$$$$=−\mathrm{2}\int\frac{{dt}}{{t}^{\mathrm{2}} −\mathrm{6}{t}−\mathrm{1}}=−\mathrm{2}\int\frac{{dt}}{\left({t}−\mathrm{3}+\sqrt{\mathrm{10}}\right)\left({t}−\mathrm{3}+\sqrt{\mathrm{10}}\right)}= \\$$$$=\frac{\sqrt{\mathrm{10}}}{\mathrm{10}}\int\left(\frac{\mathrm{1}}{{t}−\mathrm{3}+\sqrt{\mathrm{10}}}−\frac{\mathrm{1}}{{t}−\mathrm{3}−\sqrt{\mathrm{10}}}\right){dt}= \\$$$$=\frac{\sqrt{\mathrm{10}}}{\mathrm{10}}\mathrm{ln}\:\frac{{t}−\mathrm{3}+\sqrt{\mathrm{10}}}{{t}−\mathrm{3}−\sqrt{\mathrm{10}}}\:= \\$$$$=\frac{\sqrt{\mathrm{10}}}{\mathrm{10}}\mathrm{ln}\:\mid\frac{\:\mathrm{3}{x}+\mathrm{1}+\sqrt{\mathrm{10}\left({x}^{\mathrm{2}} +\mathrm{1}\right)}}{\mathrm{3}−{x}}\mid\:+{C} \\$$$$\underset{\mathrm{0}} {\overset{\mathrm{3}} {\int}}...\:\mathrm{doesn}'\mathrm{t}\:\mathrm{converge} \\$$

Answered by liberty last updated on 19/Nov/20

$${since}\:\underset{{x}\rightarrow\mathrm{3}^{−} } {\mathrm{lim}}\:\left(\mathrm{3}−{x}\right).\frac{\mathrm{1}}{\left(\mathrm{3}−{x}\right)\sqrt{{x}^{\mathrm{2}} +\mathrm{1}}}\:=\:\frac{\mathrm{1}}{\:\sqrt{\mathrm{10}}} \\$$$${it}\:{follows}\:{that}\:\underset{\mathrm{0}} {\overset{\mathrm{3}} {\int}}\:\frac{{dx}}{\left(\mathrm{3}−{x}\right)\sqrt{{x}^{\mathrm{2}} +\mathrm{1}}}\:{diverges} \\$$

Answered by Bird last updated on 19/Nov/20

$${A}\:=\int_{\mathrm{0}} ^{\mathrm{3}} \:\frac{{dx}}{\left(\mathrm{3}−{x}\right)\sqrt{{x}^{\mathrm{2}} \:+\mathrm{1}}}\:{we}\:{do}\:{the} \\$$$${changement}\:{x}={sht}\:\Rightarrow \\$$$${A}\:=\int_{\mathrm{0}} ^{{argsh}\left(\mathrm{3}\right)} \:\:\frac{{cht}}{\left(\mathrm{3}−{sht}\right){cht}}{dt} \\$$$$=\int_{\mathrm{0}} ^{{ln}\left(\mathrm{3}+\sqrt{\mathrm{10}}\right)} \:\:\:\:\frac{{dt}}{\mathrm{3}−\frac{{e}^{{t}} −{e}^{−{t}} }{\mathrm{2}}} \\$$$$=\int_{\mathrm{0}} ^{{ln}\left(\mathrm{3}+\sqrt{\mathrm{10}}\right)} \:\frac{\mathrm{2}{dt}}{\mathrm{6}−{e}^{{t}} \:+{e}^{−{t}} } \\$$$$=_{{e}^{{t}} \:={x}} \:\:\:\:\int_{\mathrm{1}} ^{\mathrm{3}+\sqrt{\mathrm{10}}} \:\:\:\:\frac{\mathrm{2}{dx}}{{x}\left(\mathrm{6}−{x}+{x}^{−\mathrm{1}} \right)} \\$$$$=\mathrm{2}\:\int_{\mathrm{1}} ^{\mathrm{3}+\sqrt{\mathrm{10}}} \:\:\:\:\:\frac{{dx}}{\mathrm{6}{x}−{x}^{\mathrm{2}} +\mathrm{1}} \\$$$$=−\mathrm{2}\int_{\mathrm{1}} ^{\mathrm{3}+\sqrt{\mathrm{10}}} \:\:\:\:\frac{{dx}}{{x}^{\mathrm{2}} −\mathrm{6}{x}−\mathrm{1}} \\$$$$\Delta^{'} \:=\mathrm{9}+\mathrm{1}=\mathrm{10}\:\Rightarrow{x}_{\mathrm{1}} =\mathrm{3}+\sqrt{\mathrm{10}} \\$$$${x}_{\mathrm{2}} =\mathrm{3}−\sqrt{\mathrm{10}}\:\Rightarrow \\$$$${I}\:=−\mathrm{2}\:\int_{\mathrm{1}} ^{\mathrm{3}+\sqrt{\mathrm{10}}} \:\:\:\:\frac{{dx}}{\left({x}−\mathrm{3}−\sqrt{\mathrm{10}}\right)\left({x}−\mathrm{3}+\sqrt{\mathrm{10}}\right)} \\$$$$=−\frac{\mathrm{2}}{\mathrm{2}\sqrt{\mathrm{10}}}\:\int_{\mathrm{1}} ^{\mathrm{3}+\sqrt{\mathrm{10}}} \:\:\:\left(\frac{\mathrm{1}}{{x}−\mathrm{3}−\sqrt{\mathrm{10}}}−\frac{\mathrm{1}}{{x}−\mathrm{3}+\sqrt{\mathrm{10}}}\right){dx} \\$$$$=−\frac{\mathrm{1}}{\:\sqrt{\mathrm{10}}}\left[{ln}\mid\frac{{x}−\mathrm{3}−\sqrt{\mathrm{10}}}{{x}−\mathrm{3}+\sqrt{\mathrm{10}}}\mid\right]_{\mathrm{1}} ^{\mathrm{3}+\sqrt{\mathrm{10}}} \:=−\infty \\$$$${this}\:{integral}\:{dkverges}..\sqrt{!} \\$$